Abused and Alone: Legal Redress for Migrant Domestic Workers in Malaysia - Whelan, Jennifer; Nordin, Rohaida; Ishak, Ma Kalthum; Matwi, Nursyuhada (UI Scholars Hub, 2016)
Malaysia’s rapid economic development has relied on Malaysian workers as well as on migrant workers, especially from ASEAN countries and South Asia. The sustained high economic growth rates in Malaysia over approximately three decades caused the increase in migrant workers, who were to meet the rising demand in certain sectors of the Malaysian labour market. The objective of the article is to identify potential opportunities for policy and legislative reform in relation to Malaysia’s implementation of its obligations as a Migrant Domestic Worker (MDW) receiving country specifically in relation to the barriers to MDW bringing claims where their rights have been breached. This article has identified the relevant policy, legislative and support mechanism (NGO and government) landscape in Malaysia regarding the realisation of the rights of migrant domestic workers in Malaysia to bring claims where their rights have been breached; best practice examples of the relevant policy, legislative and support mechanism landscapes in at least 2 ‘best practice’ MDW receiving countries regarding the realisation of the rights of MDW to bring claims where their rights have been breached; and potential opportunities for policy, legislative and support mechanism reform in Malaysia to further enhance the realisation of the rights of MDW in Malaysia specifically in relation to redress mechanisms for breaches of the rights of MDW.